Fat emulsification measured using NMR transverse relaxation. - Marciani, L; Ramanathan, C; Tyler, D; Young, P; Manoj, P; Wickham, M; Fillery-Travis, A; Spiller, R; Gowland, P (2001)
This paper presents a novel method of measuring the droplet size in oil-in-water emulsions. It is based on changes in the NMR transverse relaxation rate due to the effect of microscopic magnetic susceptibility differences between fat droplets and the surrounding water. The longitudinal and transverse relaxation rates of a series of emulsions with constant oil volume fraction and five different mean droplet sizes, in the range 0.4-20.9 microm, were measured in vitro at 37 degrees C using EPI. While the longitudinal relaxation rate 1/T(1) did not change significantly, 1/T(2) was observed to increase with mean droplet size. The measured changes in 1/T(2) were found to be in good agreement with results predicted from proton random walk simulations, and were also consistent with analytical solutions based on an outer sphere relaxation model. Measurements of 1/T(2) on emulsions with a higher oil volume fraction, and on emulsions of a fixed size where the water phase was doped with gadolinium to modulate the susceptibility difference between the phases, also showed the predicted behavior. As part of this study the susceptibility difference between olive oil and water was measured to be 1.55 ppm.